A New Reactive Thermoplastic Spacer with Excellent Durable Energy Efficiency for Structural Glazing Façades - C. Scherer (Challenging Glass Conference, 2016)
For the use in structural glazing (SSG) applications a new generation of warm edge system has been developed. This new technology is a spacer system based on polyisobutylene, especially designed for silicone sealed units, which replaces the conventional edge seal components: metal or plastic spacer, desiccant and primary sealant.  In contrast to these components, this hot applied spacer system is an integrated polymer matrix incorporating the desiccant, which meets the high requirements regarding long term stability and in particular the demands for noble gas tightness of insulating glass units (IGUs) with silicone secondary sealant. In contrast to rigid spacer frames, this new spacer generation utilizes the whole inner gap size of the IGU to absorb movements caused by environmental stresses and allows full flexibility in shape of IGU. Excellent durability of the edge seal is insured by a chemical bond of the spacer matrix to glass and silicone secondary sealants. Due to the computer controlled application and the low permeability of the spacer the IGUs fulfil the requirements of the EN 1279-3 (gas tightness) even under standard mass production process conditions. This allows for an especially easy production even of triple IGUs, large formats and free shape designs with outstanding accuracy. The innovative reactive thermoplastic spacer is a new milestone in IGU technology with excellent durable energy efficiency for façades and contributes a significant step towards energy sustainability in building envelopes.